Enterprise business modeling, optimization techniques, and flexible information systems - Papajorgji, Petraq J.; Guimarães, Alaine Margarete.; Guarracino, Mario. (IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2013)
"This book supplies a wide array of research on the intersections of business modeling, information systems, and optimization techniques, offering various business models and structuring methods"--Provided by publisher.